Imagining Manila literature, empire and orientalism - Sykes, Tom (I.B. Tauris, 2021)
Manila is one of the most important ports in Asia, uniquely sheltered by its unusual geography it has been a trading hub for centuries and at the centre of Spanish, American and British empire building. This book analyses the Anglo-American writing on the city in order to build a cultural history of the place, as well as situating it within scholarship on empire, orientalism and South-East Asian political history. Through analysis of novels, memoirs, travelogues and journalism written about Manila by Westerners since the early eighteenth century, Tom Sykes builds a picture of Western attitudes towards the city and the mechanics by which these have come to dominate the cultural history of the place. By examining Western narratives of Manila, this study uncovers to what extent these tropes have informed understandings of the Philippines, both in the West as well as in the Philippines itself, and the types of counter-narrative which have emerged in the Philippines in response to them
Keywords: Geschichte; Englisch; Literatur; Manila -- Motiv